2023
DOI: 10.3389/fenvs.2022.1028793
|View full text |Cite
|
Sign up to set email alerts
|

Reduction in energy consumption and CO2 emissions by retrofitting an existing building to a net zero energy building for the implementation of SDGs 7 and 13

Abstract: This work aims to reduce the energy consumption of existing buildings through retrofitting and converting them into net zero energy buildings (NZEBs). Various retrofits for an existing academic building were modeled and analyzed using REVIT software. Energy consumption was reduced to approximately 34% through retrofits, and a Solar System of 41.6 kW was integrated to meet the reduced energy demand, consequently converting the building into an net zero energy building (NZEB). Furthermore, environmental and econ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 33 publications
(29 reference statements)
0
1
0
Order By: Relevance
“…The above data are sufficient to illustrate the importance of conducting research on the applicability of nearly zero-energy office building technology systems for different sub-climatic zones and different cooling and heating load requirements in the HSCW zone. Nearly zero-energy buildings (nZEBs), a worldwide perspective on building energy conservation and renewable energy utilization, have earned an increasing interest in the Nearly zero-energy buildings (nZEBs), a worldwide perspective on building energy conservation and renewable energy utilization, have earned an increasing interest in the pursuit of sustainable development [39,40]. A nearly zero-energy building is a building that adapts to climatic characteristics and natural conditions, minimizes heating, cooling, and lighting needs via passive technology, maximizes the efficiency of energy equipment and systems via active technology, makes full use of renewable energy, provides a comfortable indoor environment with minimal energy consumption, and meets the standard requirements for indoor environmental parameters and energy consumption indicators [36].…”
Section: Energy Simulation Results For Baseline Buildings In Differen...mentioning
confidence: 99%
“…The above data are sufficient to illustrate the importance of conducting research on the applicability of nearly zero-energy office building technology systems for different sub-climatic zones and different cooling and heating load requirements in the HSCW zone. Nearly zero-energy buildings (nZEBs), a worldwide perspective on building energy conservation and renewable energy utilization, have earned an increasing interest in the Nearly zero-energy buildings (nZEBs), a worldwide perspective on building energy conservation and renewable energy utilization, have earned an increasing interest in the pursuit of sustainable development [39,40]. A nearly zero-energy building is a building that adapts to climatic characteristics and natural conditions, minimizes heating, cooling, and lighting needs via passive technology, maximizes the efficiency of energy equipment and systems via active technology, makes full use of renewable energy, provides a comfortable indoor environment with minimal energy consumption, and meets the standard requirements for indoor environmental parameters and energy consumption indicators [36].…”
Section: Energy Simulation Results For Baseline Buildings In Differen...mentioning
confidence: 99%
“…It is possible to conclude that both options are irreconcilable with SDG 7; at least as Mexico speeds up its transition to renewable and clean energy. With regard to this, distinguished scholars have published an array of sustainability solutions to increase the reliability and variability of renewable energy that Mexican policymakers could adopt to strengthen the current energy laws [54][55][56]. Still, this topic is beyond the scope of this article.…”
Section: Discussionmentioning
confidence: 99%
“…However, several case studies have shown that NZEB retrofits with passive strategies, including optimizing envelope insulation, heating and lighting systems, shading and controls, can transform them into viable environmental options. These passive design interventions reduce CO 2 emissions and can also provide energy and environmental payback times shorter than the building's life cycle [83][84][85]. Ohene et al [84] indicated that introducing solar PV technology to retrofitted buildings can even generate net positive energy, facilitating buildings converted to NZEBs within the payback period.…”
Section: Sustainable Trends and Clusters Of Nzebsmentioning
confidence: 99%